Mathematic’s models in metabolic engineering - Szewczyk, Krzysztof W. (Committee on Biotechnology PAS, 2005)
Metabolic engineering is an integrating methodology of analysis and synthesis for improvement of flux distribution of metabolic pathways. It has two main aspects: modeling and analysis of metabolic networks to establish strategies for pathway engineering and actual molecular level engineering the pathway. Mathematical modeling is one of the key methodologies of metabolic engineering. The review presents the currently used metabolic modeling approaches. Metabolite balancing is the basis for analysis of metabolic flux and cell capability to form a targeted product. The use of isotope - labeled substrates with nuclear magnetic resonance (NMR) and gas chromatography-mass spectrometry (GCMS) analyses of intracellular and extracellular metabolites enables determination of metabolic flux distribution. Metabolic Control Analysis (MCA) is a theoretical framework for investigation of control mechanism of metabolic network to identify key parameters influencing productivity. Kinetics models present a more detailed approach to simulate metabolic net behavior. Linear approximation of kinetic model, the so called (log)linear kinetics, is useful for modeling spatiotemporal variations of the net. The including of genetic regulation to metabolic models, the next step in the development of metabolism models, needs new methods of experimental approaches and mathematic and computational resources.
Keywords: biotechnology